Genotyping Tinea Capitis Fungi based on Barcoding ITS rDNA Marker (Medico Legal Update, 2020)
The study included isolating and diagnosing of Tinea capitis fungi isolated from clinical samples who arevisited the outpatient clinics in Babylon / Hilla province. 50 samples were collected 40 clinical samples(hairs and scales), and 10 hair samples as control group. The results showed that: numbers of dermatophytesfungi were identified based on microscopic and Molecular criteria. T. mentagrophytes, T. tonsurans, M. audounii, M. canis. . Also two yeast species were identified: Candida albicans, Candida parapsilosis.